HYPERTENSION THERAPY USING ACUPUNCTURE AND HERBALS OF LEDS AND CARROTS - Khasanah, Ulfa Nur; Imandiri, Ario; Adianti, Myrna (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in rest or quiet state. Hypertension in Traditional Chinese Medicine (TCM) is categorized in Xuan Yuan (vertigo) and Tou Tong (headache). Purpose: To determine the effect of acupuncture therapy using Fengchi (GB20), Taichong (LR3), Hegu (LI4) points and 2 additional points, namely Xuehai (SP10) and Chize (LU5) and herbs therapy for celery (Apium graveolens L.) and carrots (Daucus carota L.) for people with hypertension. Method: Treatment of hypertension with acupuncture and herbs therapy. Acupuncture therapy was carried out at Fengchi (GB20), Taichong (LR3), Hegu (LI4) points with the principle of liver fire sedation and Xuehai (SP10) and Chize (LU5) with the tonification principle. In herbs therapy, patients were given fresh celery (Apium graveolens L.) and carrots (Daucus carota L.) which had a hypotensive effect. Result: Hypertension treatment with acupuncture therapy was given 12 times, 3 times a week. Herbs therapy was given for 4 weeks, taken once a day in the afternoon with a dose of 200 ml. This therapy could reduce the patient's blood pressure. Conclusion: Acupuncture therapy in Fengchi (GB20), Taichong (LR3), Hegu (LI4) Xuehai (SP10), Chize (LU5) plus fresh celery herbs (Apium graveolens L.) and carrots (Daucus carota L.) could reduce blood pressure and additional complaints in hypertensive patients